A Regional, Honey Bee-Centered Approach Is Needed to Incentivize Grower Adoption of Bee-Friendly Practices in the Almond Industry - Durant, Jennie L.; Ponisio, Lauren C. (Frontiers in Sustainable Food Systems, 2021)
Managed and wild bee populations contribute over 15 billion in pollination services to US agriculture, yet both are declining or becoming increasingly vulnerable to parasites and disease. The loss of healthy and diverse forage is a key driver in bee declines, so incentivizing land managers to adopt diversified bee-friendly management practices such as forage plantings and reduced pesticide use can directly increase food security, pollinator health, and farmer adaptive capacity. To better understand what might incentivize growers to adopt bee-friendly practices, we conducted a survey of California almond growers, whose orchards are entirely dependent on bee pollination and draw nearly 88% of US bee colonies each February to pollinate almond bloom. We asked 329 respondents across all major almond growing regions of CA about their adoption rate and incentives for planting cover crops, pollinator habitat, and practicing the recommended and legally required bee-friendly best management practices, as well as their interest in bee-friendly certification programs. Using a model selection framework, we evaluated which geographic, social, operational, and pollination-service related factors were predictive of bee-friendly practice adoption. We found that no single factor was a statistically significant predictor of adoption across all models, suggesting there is no silver bullet determining bee-friendly practice adoption. However, we discovered that region and concerns about future pollination services consistently emerged as important factors related to all the practices we investigated, except the adoption of legally required BMPs. These findings suggest that a regionally flexible pollinator conservation strategy focused on supporting honey bee colonies might have the highest likelihood of grower participation and adoption.